The Rise of Tech Corporation In Indonesia: Are Tech IPOs Priced Differently? - Kuswanto, Randy (Universitas Pendidikan Nasional, 2024)
This research investigates whether technology IPOs in Indonesia are priced differently compared to non-technology IPOs, focusing on their post-IPO returns at various time points (T+1, T+7, T+30, T+90, and T+180). The study utilizes a sample of 325 IPO firms, including 33 technology firms, that went public between 2017 and 2023. Using the Mann-Whitney U test, the research analyzes differences in stock returns between technology and non-technology sectors. The results indicate no statistically significant differences in returns at any of the observed time points, challenging the common assumption that technology IPOs are subject to higher underpricing due to higher uncertainty and growth potential. The findings suggest that market conditions, information transparency, and governance mechanisms may have mitigated sector-specific pricing differences. This research contributes to the literature on IPO pricing by providing evidence from an emerging market context and offers valuable insights for investors and policymakers regarding the dynamics of IPO pricing in Indonesia.